Prognostic significance of TERT promoter and BRAF mutations in TIR-4 and TIR-5 thyroid cytology. Issue 1 (July 2019) - Censi, Simona; Barollo, Susi; Grespan, Elisabetta; Watutantrige-Fernando, Sara; Manso, Jacopo; Iacobone, Maurizio; Casal Ide, Eric; Galuppini, Francesca; Fassina, Ambrogio; Bertazza, Loris; Vianello, Federica; Pennelli, Gianmaria; et al.
Abstract : Objective: Follicular-derived thyroid cancers generally have a good prognosis, but in a minority of cases, they have an aggressive behavior and develop distant metastases, with an increase in the associated mortality. None of the prognostic markers currently available prior to surgery can identify such cases. Methods: TERT promoter and BRAF gene mutations were examined in a series of 436 consecutive TIR-4 and TIR-5 nodes referred for surgery. Follow-up (median: 59 months, range: 7–293 months) was available for 384/423 patients with malignant nodes. Results: TERT promoter and BRAF mutations were detected in 20/436 (4.6%) and 257/434 thyroid nodules (59.2%), respectively. At the end of the follow-up, 318/384 patients (82.8%) had an excellent outcome, 48/384 (12.5%) had indeterminate response or biochemical persistence, 18/384 (4.7%) had a structural persistence or died from thyroid cancer. TERT promoter mutations correlated with older age ( P < 0.0001), larger tumor size ( P = 0.0002), oxyntic and aggressive PTC variants ( P = 0.01), higher tumor stages ( P < 0.0001), distant metastases (<0.0001) and disease outcome ( P < 0.0001). At multivariate analysis, TERT promoter mutation was not an independent predictor of disease outcome. TERT promoter mutation- (OR: 40.58; 95% CI: 3.06–539.04), and N1b lymph node metastases (OR: 40.16, 95% CI: 3.48–463.04) were independent predictors of distant metastases. BRAF mutation did not predict the outcome, and it correlated with a lower incidence of distant metastases ( P = 0.0201). Conclusions: TERT promoter mutation proved an independent predictor of distant metastases, giving clinicians the chance to identify many of the patients who warranted more aggressive initial treatment and closer follow-up.